Children´s bone marrow transplantation in Peru - Rodríguez Zúñiga, Milton José Max (2014)
The bone marrow transplant (BMT) is a costly and complex procedure in which healthy bone marrow from a donor are infused into the bloodstream of a recipient, who will be their bone marrow destroyed with radiation and / or chemotherapy. The TMO was first reported in animals in 1951, and successfully in humans in 1968 in the United States of America (USA).